Developing Hajj and Umrah Materials Through Canva-Based Interactive E-modules to Improve Student Learning Outcomes - Lusiana; Suparwoto Sapto Wahono; St Rodliyah (Tarbawi : Jurnal Ilmu Pendidikan, 2025)
This study aimed to evaluate the validity, feasibility, and effectiveness of Fiqh learning materials on Hajj and Umrah delivered through a Canva-based interactive e-module for Grade VIII students at MTs As-Shiddiqy Pakis Panti Jember. The study followed a systematic instructional design process encompassing analysis, design, development, implementation, and evaluation phases. The effectiveness test was conducted using a One-Group Pretest–Posttest Design in a limited field trial involving 20 students. The research instruments included expert validation sheets for content and media, student response questionnaires, and learning achievement tests that had undergone rigorous validity and reliability testing. Data analysis was performed using the Shapiro–Wilk normality test, paired-sample t-test, and N-Gain calculation. The results indicate that: (1) validation from content, media, and user (student) experts categorized the interactive e-module as highly valid with an average score of 84; (2) the learning materials were found to be highly feasible with an average score of 83; and (3) the interactive e-module significantly improved learning outcomes, as evidenced by an increase in average scores from 43 (pretest) to 82 (posttest)—the N-Gain value of 0.675 falls into the medium–high category. In conclusion, the Canva-based interactive e-module for Fiqh learning is a valid, feasible, and effective tool for enhancing student achievement